The Effects of a Transgelin-2 Agonist Administered at Different Times in a Mouse Model of Airway Hyperresponsiveness - Yuan, Hong-Kai; Lu, Jin; Wang, Xue-Ling; Lv, Zhi-Ying; Li, Bo; Zhu, Weiliang; Yang, Yong-Qing; Yin, Lei-Miao (Frontiers in Pharmacology, 2022)
Airway hyperresponsiveness (AHR) is one of the most important features of asthma. Our previous study showed that inhaled transgelin-2 agonist, TSG12, effectively reduced pulmonary resistance in a mouse model of asthma in a dose dependent manner. However, the optimal administration time of TSG12 to reduce AHR and the pharmacological effects are still unclear. In this study, the effects of TSG12 inhalation before and during AHR occurrence were examined. The results showed that the pulmonary resistance was reduced by 57% and the dynamic compliance was increased by 46% in TSG12 Mch group (atomize TSG12 10 min before methacholine, P < 0.05 vs model). The pulmonary resistance was reduced by 61% and the dynamic compliance was increased by 47% in TSG12+Mch group (atomize TSG12 and methacholine together, P < 0.05 vs model). Quantitative real-time PCR showed that the gene expression levels of transgelin-2, myosin phosphatase target subunit-1 and myosin light chain were up-regulated 6.4-fold, 1.9-fold and 2.8-fold respectively in TSG12 Mch group. The gene expression levels of transgelin-2, myosin phosphatase target subunit-1 and myosin light chain were up-regulated by 3.2-fold, 1.4-fold and 1.9-fold respectively in TSG12+Mch group. The results suggested that TSG12 effectively reduce pulmonary resistance when TSG12 inhalation both before or during AHR occurrence. Gene expression levels of transgelin-2 and myosin light chain were significantly up-regulated when TSG12 inhalation before AHR occurrence. This study may provide a basis for the administration time of TSG12 of asthma treatment in the future.